ISOLATION AND CHEMICAL CHARACTERIZATION OF BIOACTIVE ALKALOID FROM ARGYREIA SPECIOSA LINN. HAVING ACTION ON ISOLATED RAT LEYDIG CELLS - NIRAJ VYAS; KANAN GAMIT; MANAN RAVAL; SAMIR PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Present study was aimed to isolate and chemically characterize bioactive constituent from alkaloid enriched fraction, prepared from roots of Argyreia speciosa Linn. Materials and methods: Literature review revealed presence of ergoline type of alkaloids in roots. Alkaloidal fraction was prepared and screened for its action on testosterone biosynthesis, in- vitro, using isolated rat leydig cells. Dehydroepiandosterone was used as positive control. This bioactive fraction was subjected to open column chromatography followed by flash chromatography, to isolate constituent. One compound (A1) was isolated from the fraction and its purity was ascertained using TLC and HPLC studies. A1 was chemically characterized by IR, Mass and 1H-NMR studies, to elucidate probable chemical structure. A1 was screened for action on testosterone synthesis too, using isolated rat Leydig cells model. The fraction was standardized with respect to amount of A1 present. Results: Alkaloidal fraction (1000 µg/ml) incubated Leydig cells showed nearly, 22 fold increase in testosterone content as compared to untreated cells. The studies also yielded increase in testosterone content, in cells treated with test fractions and as observed in case of positive control. TLC studies indicated that A1 might possess ergoline moiety in the structure. IR, Mass and 1H NMR spectral studies suggested that A1 might be N-methyl ergometrine. This was the first report included isolation and chemical characterization of N-methyl ergometrine from Argyreia speciosa. A1 (1000 µg/ml) was found to stimulate testosterone content, by 14.62 fold, in culture media of Leydig cells after incubation. Conclusion: The results of in vitro studies, confirmed that the standardized alkaloid fraction as well as A1 had ability to stimulate Leydig cells to secrete testosterone. A1 might be N-methyl ergometrine and being ergometrine derivative it might act through oxytocine receptors expressed on the Leydig cells and stimulates testosterone synthesis.